The transitioning process: A qualitative case study of international swimming and diving student-athletes competing in the NCAA - Otto, M.; Martinez, M.; Barnhill, C. (Journal of Amateur Sport, 2020)
Prior studies examining international student-athletes` transition experiences to life on American colleges campuses have generally focused on outcomes related to their recruiting experience and change adaptation. Few studies included the adjustment process and challenges faced by the individuals. The primary purpose of this case study was to add to the existing literature by expanding on the psychological transition process of international swimming and diving student-athletes experience after joining an American intercollegiate athletics team. Utilizing Bridges (1986) model, the present study employed semi-structured interviews amongst 10 international student-athletes from a large NCAA Division I university. A thematic analysis revealed seven major themes, which were: realization that change was necessary, reflecting on the decision, language barrier, education system, cultural adjustment and valuable lessons,international bond, and words of wisdom. The findings suggested transition is a multi-stage process that occurs throughout student-athletes` experiences on campus.